Morfologi dan Morfometrik Jenis Ikan Gobi di Danau Limboto - Rauf, Yuliana; Sahami, Femy Mahmud; Kadim, Miftahul Khair (The NIKe Journal, 2024)
This research aims to determine the morphological and morphometric characteristics of goby fish species in Lake Limboto, Gorontalo Regency. Sampling was carried out at 3 (three) fishing boat landing locations on Lake Limboto, namely in Huntu Village, Bua Village and Iluta Village. Sampling was carried out from April to June 2021. The samples collected were all types of gobies caught by fishermen in Lake Limboto. All samples were observed and grouped based on their morphological similarities and then morphometric measurements were carried out using the ImageJ application. The results of the research showed that in Lake Limboto there were 3 groups of gobies found, morphologically namely manggabai (Glossogobius) there were 3 groups, Hulu'u (Ophieleotris) 3 groups and tola-tola/gabus (Channa) only 1 group, and morphometrically the manggabai group has distinguishing characteristics in the form of body height and anal fin length, Hulu'u's distinguishing characteristics are eye diameter and tail fin length, while tola/tola/gabus are not compared.